Alternative control of raspberry postharvest decay - Antoniolli, Lucimara Rogéria; da Silva, Gildo Almeida; Alves, Silvio André Meirelles; Moro, Laís (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the effect of pre-harvest treatments on post-harvest decay and on quality of 'Heritage' raspberries (Rubus idaeus L.). Fruit were sprayed with one of the following treatments: distilled water (control), 6 g L-1 of chitosan, 100 mg L-1 of chlorine dioxide solution, Bacillus amyloliquefaciens, Curtobacterium pusillum or Saccharomyces cerevisiae suspensions. Harvest was done at 3, 7, and 14 days after spray treatment. After each harvest, at commercial maturity (when fruit were pink), fruit were individually inoculated with conidial suspension (2x105 conidia mL-1) of Botrytis cinerea or Rhizopus stolonifer. Fruit were kept at 12±0.5ºC for seven days and were evaluated for decay and main quality attributes. Bacillus amyloliquefaciens, C. pusillum, and S. cerevisiae provided smaller area under disease progress curve of decays caused by Botrytis and Rhizopus. The biological control agents evaluated do not adversely affect fruit quality attributes, and, therefore, are potential alternatives to control post-harvest decay of raspberries.
Keywords: Bacillus amyloliquefaciens; Curtobacterium pusillum; Rubus idaeus L.; Saccharomyces cerevisiae; biological control; berries; chitosan